DYNAMIC SIMULATION OF RUBBER PRODUCTION SYSTEMS USING SSM AND VENSIM APPROACHES - HAFIZA APRILIA (Universitas Majalengka, 2024)
One of the contributors to the agricultural sector, particularly in the plantation sub-sector, is the rubber industry, which accounts for 38.54% of Indonesia's rubber exports. This opportunity arises from the fact that 85% of rubber producers are smallholder farmers, while the remaining share is owned by state and private enterprises. Makmurman is an individual rubber business owner based in South Sumatra Province, with a 4-hectare rubber plantation that directly sells raw rubber to collectors. The rapid advancement of technology in modern life has led to increased use of elastic materials, thereby driving higher demand for rubber, especially in the automotive industry. As a result, Makmurman has experienced a surge in demand for raw rubber from collectors. However, Makmurman has been unable to meet this demand, likely due to the many variables involved in the production process and the sale of raw rubber, which have created challenges. To address these issues, a root cause analysis is conducted to identify the appropriate solution using the soft system methodology approach. Additionally, data processing is carried out using Vensim software to model the rubber production system in a real-world scenario. The results include the development of causal loop diagrams and stock flow diagrams. The expected outcome is a dynamic system simulation with various scenarios, ultimately identifying the best scenario that ensures the highest availability of rubber for Makmurman to meet the demands of the rubber collectors.